The Law and Question. The Phenomenon of Question as a Possible Point of Departure for the Phenomenologico-Genetic Theory of Law - Sobota, Daniel Roland (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
In his original phenomenology of law Adolf Reinach distinguishes among experiences the so-called “social acts”. These include acts directed towards other persons that require that the latter acknowledge the communicated contents and assume certain attitudes. Among these acts Reinach mentions there are promises, orders, requests and questions. He argues the promise is the special act that creates the a priori grounds of law. It is to be noted that Reinach’s phenomenology of law is of static character (in the Husserlian sense of the word) and therefore it shares all its advantages and disadvantages. In my paper I would like to draw attention to another social act, which can also be attributed to certain law-making activities, especially from the perspective of the genetic phenomenology. It is questioning. At the same time when Reinach was working on his theory of law, his Munich friend, Johannes Daubert (1877–1947), also a student of Theodor Lipps and a friend of Edmund Husserl, who together with Reinach made an “invasion of the Munichs at Göttingen”, worked on the first phenomenology of the question. Although he did not refer his research to the phenomenon of law, we can ask whether, like Reinach’s deliberations about promises and obligation, it cannot be done. That this is possible to some extent, for example, is evinced by the Hannah Arendt and Klaus Held’s phenomenology of the political world. He points out that the public world as such arises from the primordial openness of man, understood as “zoon politikon”. This openness might be interpreted as the question which is not so much a single act as it is an attitude. The purpose of the paper is to outline how, while starting with the phenomenological reflection over various types of utterances, one can specify their certain forms and the acts constituting them as well as the attitudes which allow for a priori grounding the phenomenon of law from the perspective of static and genetic phenomenology.